2004
DOI: 10.1149/1.1804812
|View full text |Cite|
|
Sign up to set email alerts
|

A Mathematical Model for the Lithium-Ion Negative Electrode Solid Electrolyte Interphase

Abstract: The passivating solid electrolyte interphase ͑SEI͒ layer forms at the surface of the negative-electrode active material in lithium-ion cells. A continuum-scale mathematical model has been developed to simulate the growth of the SEI and transport of lithium and electrons through the film. The model is used to estimate the film growth rate, film resistance, and irreversible capacity loss due to film formation. We show that film growth at the negative electrode is faster for charged batteries than for uncharged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
240
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(246 citation statements)
references
References 54 publications
5
240
1
Order By: Relevance
“…Surface reactions will lead to a modification of the interface conditions. Transport within a SEI requires the addition of another thermodynamic phase with appropriate transport coefficients [38]. Volumetric reactions require the inclusion of the reacting species and the information on the reaction kinetics [20].…”
Section: Discussionmentioning
confidence: 99%
“…Surface reactions will lead to a modification of the interface conditions. Transport within a SEI requires the addition of another thermodynamic phase with appropriate transport coefficients [38]. Volumetric reactions require the inclusion of the reacting species and the information on the reaction kinetics [20].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 However, Etacheri et al showed that substantial improvement can be achieved by using fluoroethylene carbonate (FEC) as electrolyte additive, which significantly reduces irreversible capacities and leads to improved cycling stability. 22 In particular, a reduction of the irreversible capacity by roughly 50% was observed when FEC was used in comparison to FEC-free electrolytes.…”
mentioning
confidence: 99%
“…19 Even though the particle cracking can be prevented, mathematical modeling suggests that the SEI formed on the silicon particles cracks during the volumetric changes, causing a continuous electrolyte consumption and loss of active lithium. 20,21 However, Etacheri et al showed that substantial improvement can be achieved by using fluoroethylene carbonate (FEC) as electrolyte additive, which significantly reduces irreversible capacities and leads to improved cycling stability. 22 In particular, a reduction of the irreversible capacity by roughly 50% was observed when FEC was used in comparison to FEC-free electrolytes.…”
mentioning
confidence: 99%
“…[43][44][45][46][47][48][49] J. Newman has conducted very detailed analysis of porous carbon electrodes in non-aqueous LIB electrolytes. [45][46][47][48][49] Some limiting cases have been demonstrated depending on the porosity (pore size distribution, electrolyte concentration, etc).The most common and fundamental source of capacity fade in successful Li-ion batteries (which manage to resist degradation over hundreds of cycles) is the loss of lithium to the solid-electrolyte interphase (SEI), which typically forms at the negatively charged electrode during recharging. 50 NIBs and LIBs are both subject to the same limitations in the anode-electrolyte interfacial reaction; the solid electrolyte interphase (SEI) on an anode with the electrochemical potential below ∼1 V vs Na/Na + is vital to make a NIB kinetically stable.…”
mentioning
confidence: 99%